The zombie chasers - Kloepfer, John.; Wolfhard, Steve (New York : HarperCollinsPublishers, 2010)
When zombies take over Phoenix, Arizona, Zack Clarke, his best friend Rice, and his older sister's mean friend Madison Miller team up to try to defeat the undead, or at least survive one another.
Keywords: Zombies; Survival; Horror stories